DIGITAL TOOLS AND PLATFORMS IN EFL TEACHING: A NEW ERA OF LANGUAGE INSTRUCTION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
The integration of digital tools and online platforms in English as a Foreign Language (EFL) education has transformed traditional language instruction into a dynamic, student-centered, and interactive experience. This paper explores the role and impact of various digital technologies such as learning management systems (LMS), mobile applications, gamification tools, and artificial intelligence in EFL classrooms. The study examines how these tools enhance language acquisition, student engagement, and personalized learning. The findings suggest that technology-based instruction fosters greater motivation, learner autonomy, and improved vocabulary and communication skills.